2022
DOI: 10.1183/23120541.00202-2022
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic smokers without COPD have physiological changes heralding the development of COPD

Abstract: BackgroundChronic Obstructive Pulmonary Disease (COPD) is a major health problem, mainly due to cigarette smoking. Most studies in COPD are dedicated to fully developed COPD in older subjects, even though development of COPD may start soon after smoking initiation. Therefore, there is a need to diagnose this “early disease” by detecting the initial events responsible for ultimate development of COPD.MethodsMeasurement of maximum mid expiratory flow between 25–75 of vital capacity (MMEF) in a routine spirometry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 40 publications
1
6
0
1
Order By: Relevance
“…Our study has limitations. It was a cross-sectional study but the value of FEF 25-75 as a monitoring tool has also been demonstrated longitudinally15 21 22 and our study provided a larger sample confirming the prevalence of low FEF 25-75 in smokers with and without AL. FEF 25-75 is a highly variable spirometric measure but we used FEF 25-75 z-score to optimise the interpretive accuracy.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Our study has limitations. It was a cross-sectional study but the value of FEF 25-75 as a monitoring tool has also been demonstrated longitudinally15 21 22 and our study provided a larger sample confirming the prevalence of low FEF 25-75 in smokers with and without AL. FEF 25-75 is a highly variable spirometric measure but we used FEF 25-75 z-score to optimise the interpretive accuracy.…”
Section: Discussionsupporting
confidence: 73%
“…We hypothesised that low FEF 25-75 , would be ubiquitous in patients with AL, as this has been demonstrated to precede the development of AL 21 22. Furthermore, we hypothesised that patients with low FEF 25-75 but without AL would have physiological indicators of the risk of developing AL, even after the correction for potential confounders such as smoking history.…”
Section: Introductionmentioning
confidence: 98%
“…During follow-up, 14% of smokers with noCOPD developed COPD, of which 63% did not have CB and 37% had it, indicating that in this population, having CB does not affect the FEV 1 decline neither is it a risk factor for the eventual development of COPD. Contrary to the noCOPD, the FEV 1 decline in COPD smokers was dependent in part on the presence of CB, since COPD with CB decline more than COPD without CB (41 ± 48 vs. 22 ± 53 mL/year; p < 0.01, Table 2 ), and in part on the smoking activity, which further accelerates the FEV 1 decline [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…An explanation for this symptom probably resides in the extra amount of ventilation necessary for any degree of work even in noCOPD smokers, as demonstrated in a recent report [ 24 ]. These smokers might have early airway abnormalities and abnormal DLco, secondary to gas exchange abnormalities aggravated by the presence of CB, explaining the presenting symptoms [ 18 ]. Interestingly, the percentage of patients with a severity of dyspnoea above mMRC ≥ 2 was similar in chronic bronchitis with and without COPD, probably due to the fact that smokers noCOPD were able to exercise more than smokers with COPD, thus experimenting similar degrees of dyspnoea for a heavier exercise load.…”
Section: Discussionmentioning
confidence: 99%
“…Эпидемиологические исследования показывают, что в России распространенность ХОБЛ среди лиц с респираторными симптомами составляет 21,8 %, а в общей популяции -15,3 % [6,14]. 65 % курящих имеют патологические изменения в легких, которые могут привести к ХОБЛ [13]. Даже у тех длительно курящих людей, которые считают себя здоровыми, выраженные нарушения бронхиальной проходимости отмечались в 15 % случаев [5].…”
unclassified